Missed Opportunities for Prevention of Perinatal Transmission of Hepatitis B: A Retrospective Cohort Study - Julie van Schalkwyk; Melica Nourmoussavi; Andrea Massey; Reka Gustafson; Elizabeth Brodkin; Martin Petric; Mel Krajden; Simon Dobson; Jane Buxton; Mark Bigham; Neora Pick; Richard Schreiber; et al. (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Perinatal transmission of hepatitis B virus (HBV) can occur despite postexposure prophylaxis (PEP). Recent literature suggests that antiviral treatment during pregnancy when maternal HBV DNA levels are elevated can further decrease vertical transmission. However, HBV DNA screening is not routinely performed antenatally.